Determinants of Bank Mu'amalat Indonesia's Non-Performing Financing: Internal and External Reviews - Asiyah, Binti Nur; Septiana , Ayuk; Wahyudi, Amin (LPPM Universitas Terbuka, 2022)
Non-Performing Financing (NPF) in the management of Islamic Banks Financing needs to be controlled, although it is difficult to avoid it. This review can be observed from various internal and external variables of Islamic banks. This paper intends to analysis the determinants of Bank Muamalat's NPF, in terms of internal variables, namely Capital Adequacy Ratio (CAR), Operational Income to Operating Costs (BOPO), and Financing To Deposit Ratio (FDR), while external reviews include inflation and the Rupiah Exchange Rate. Writing method with a quantitative approach, the type of associative research. The population is taken from the financial statements of PT. Bank Muamalat Indonesia for the 2013-2021 period as many as 35 data. The sampling technique used is saturated sampling. The analysis uses multiple linear regression through normality test, classic assumption test, t test, F test and coefficient of determination test. Findings showed that CAR had a significant negative effect on NPF, BOPO had a significant positive effect on NPF, FDR had no significant effect on NPF, Inflation had no significant effect on NPF, Rupiah exchange rate had no significant effect on NPF, while CAR, BOPO, FDR, inflation, and The Rupiah exchange rate simultaneously has a significant effect on the NPF of 41%, while the rest is influenced by other indicators. Internally, CAR and BOPO have a significant effect while external reviews have no significant effect. The practical implication of this paper is that Islamic banks need to pay attention to internal conditions so that NPF can be controlled